Teologi Kristen dan Tantangan Etis dari Budaya Viral Challenge di Ruang Virtual - Rahayu, Yohana Fajar; Sumual, Elisa Nimbo (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2025)
The development of digital culture has given rise to the phenomenon of viral challenges, which have not only become an entertainment trend but also shaped the mindset and behaviour of contemporary society. This dynamic has had a significant impact on moral values, particularly when the challenges that circulate normalise risky behaviour and erode norms of propriety. The massive viral challenge phenomenon in virtual space reveals an ambivalence between positive creativity and the potential for moral degradation due to the removal of cultural and religious norms. The purpose of this study is to examine the ethical challenges of viral challenge culture from a Christian theological perspective and to formulate its implications for the life of faith. Using a qualitative method based on literature study with theological-ethical analysis of contemporary digital phenomena, it can be concluded that the viral challenge culture in a social and digital perspective shows how digital trends shape new patterns of interaction and values in modern society. However, the ethical challenges of viral challenges for Christian life reveal issues of misguided self-existence, social pressure, and the banality of sin that demand faithfulness. Therefore, the Christian theological response to viral challenge culture and its implications for Christian leadership and education in virtual spaces is important in order to provide an ethical framework, spiritual examples, and educational strategies that can correct and transform digital culture into a means of Christian service and witness.AbstrakPerkembangan budaya digital telah melahirkan fenomena viral challenge yang tidak hanya menjadi tren hiburan, tetapi juga membentuk pola pikir dan perilaku masyarakat kontemporer. Dinamika ini membawa dampak signifikan terhadap nilai moral, khususnya ketika tantangan yang beredar menormalisasi perilaku berisiko dan mengikis norma-norma kepatutan.   Fenomena viral challenge yang masif di ruang virtual memperlihatkan ambivalensi antara kreativitas positif dan potensi degradasi moral akibat menyingkirkan norma budaya dan agama. Tujuan penelitian ini adalah untuk menelaah tantangan etis dari budaya viral challenge melalui perspektif teologi Kristen serta merumuskan implikasinya bagi kehidupan iman. Menggunakan metode kualitatif berbasis studi pustaka dengan analisis teologis-etis terhadap fenomena digital kontemporer, maka dapat disimpulkan bahwa budaya viral challenge dalam perspektif sosial dan digital menunjukkan bagaimana tren digital membentuk pola interaksi dan nilai baru dalam masyarakat modern. Namun, tantangan etis viral challenge bagi kehidupan Kristen menyingkap persoalan eksistensi diri yang salah arah, tekanan sosial, serta banalitas dosa yang menuntut kewaspadaan iman. Karena itu, respon teologi kristen terhadap budaya viral challenge dan implikasi kepemimpinan dan pendidikan Kristen di ruang virtual menjadi penting untuk menghadirkan kerangka etis, teladan rohani, serta strategi edukatif yang mampu mengoreksi sekaligus mentransformasi budaya digital menjadi sarana pelayanan dan kesaksian Kristen.